Data-enabled iterative learning control: A zero-sum game design for time-scale-varying tasks - Zhuang, Zhihe; González, Rodrigo A.; Tao, Hongfeng; Paszke, Wojciech (1975- ); Oomen, Tom
Iterative learning control (ILC) is an intelligent control methodology for tackling iteration-invariant exogenous inputs. It is of great significance to develop its extrapolation for more general repetitive tasks with mutual similarity, e.g., tasks with different time scales. In practice, discrete-time ILC with sampling behavior for time-scale-varying tasks suffers from the failure of perfect corresponding learning and environment-dependent iteration-varying disturbances.
Keywords: iterative learning control; time-scale-varying task; data-based control; reinforcement learning